PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED, READING AND COMPOSTION (CIRC) MATA PELAJARAN SEJARAH GUNA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS XI IPS 2 SEMESTER GANJIL DI MA NURUL HIKAM - Raudhatul Jannah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
Student learning activities is one of the action that affect learning in the learningoutcoomes achieved by student. There ara many models of learning are less aroused teacher and student learning activities student will eventually get bored while following the learning process in the classroom. The research object class XI IPS2 were 30 students. Hopkins reseach design scheme using four phases : planning, action, observation and reflection. To obtain reseach data using the method of observation, interview, and test. Data analysis in this study used a qulitative descriptive analysis.Reseaech by implementing Cooperative Learning Cooperative Integrated Type, Reading and Compostion (CIRC) is divided into two cycles can be seen there is an incrase in activity and learning outcomes. First cycle of learning activities of student in the learning process is quite active and student learning outcomes increased by 8,88%. Cassical completeness cycle I by 80%. Student learning outcomes cycle I, still can not be said to be completed in the classical then continued learning in cycle II, students learning activities category, increased yield learning cycle I and cycle II increased by 6,67% and the classical completness result in cycle II was 86,67%. With the achievement of mastery learning classical derived class XI IPS-2 MA Nurul Hikam it is not necessary futher action cycle again.